Identification of a novel herpesvirus associated with a penile proliferative lesion in a beluga (Delphinapterus leucas) - Bellehumeur, Christian; Lair, Stéphane; Romero, Carlos H.; Provost, Chantale; Nielsen, Ole; Gagnon, Carl A. (Journal of Wildlife Diseases, 2015)
The carcass of an adult male beluga (Delphinapterus leucas) was found beach cast in 2008 on the shore of the St. Lawrence Estuary at Rivière-Ouelle, Quebec, Canada. The carcass was transported to the Faculté de médecine vétérinaire of the Université de Montréal for postmortem examination. Aspiration pneumonia was the probable cause of death. Necropsy revealed a focal papilloma-like penile lesion, characterized by focal mucosal thickening with disorganization of the epithelial layers and lymphoplasmacytic infiltration. A pan-herpesvirus nested PCR assay on frozen tissue from the penile lesion was positive. The PCR product sequencing revealed a partial herpesvirus DNA polymerase (DPOL) gene sequence of 600 nucleotides. Its nearest nucleotide identity was with the partial DPOL gene of an alphaherpesvirus, bovine herpesvirus 5 (79.5% identity). It also shared high identity with several other marine mammal herpesviruses (50.2 to 77.3% identity). This new herpesvirus was tentatively named beluga whale herpesvirus (BWHV). Virus isolation was unsuccessful. The pathogenic potential of BWHV is unknown, but the evaluation of archived tissues suggests that the virus is endemic in the St. Lawrence Estuary beluga population.